Effects of the Intraneural and Subparaneural Ultrasound-Guided Popliteal Sciatic Nerve Block: A Prospective, Randomized, Double-Blind Clinical and Electrophysiological Comparison. Issue 4 (July 2016) - Cappelleri, Gianluca; Cedrati, Valeria Libera Eva; Fedele, Luisa Luciana; Gemma, Marco; Camici, Laura; Loiero, Mario; Gallazzi, Mauro Battista; Cornaggia, Gabriele
Abstract : Background and Objectives: This prospective, randomized, double-blind study compared the effects of the ultrasound-guided popliteal sciatic nerve block performed by either intraneural or subparaneural approach followed by an electrophysiological evaluation. We hypothesized that intraneural injection provides a faster onset with a better success rate compared with the subparaneural approach. Methods: Eighty-eight patients were enrolled and randomized to receive an ultrasound-guided popliteal sciatic nerve block injecting 15 mL ropivacaine 1% according to an intraneural injection (group INTRA = 44) or a subparaneural injection (group SUBPARA = 44). The primary end point was the onset time of sensory and motor block, whereas secondary end points were successful, duration of the block, and the variation of the electrophysiological assessment after 5 weeks. The study was registered prior to patient enrollment (clinicaltrials.gov identifier NCT01987128). Results: The median onset time for successful sciatic nerve block in the INTRA group was 10 (5–15 [5–30]) minutes versus 25 (15–35 [5–45]) minutes in the SUBPARA group ( P < 0.001), with a rate of 41/43 (95.3%) compared with 25/40 (62.5%) in the SUBPARA group ( P < 0.001). No difference was found regardless of the duration of the block. Fifty-three patients also performed the electrophysiological assessment at 5 weeks, showing a subclinical, significant reduction in amplitude of the action potentials with no difference between groups. No patients reported any clinical neurological complications after 6 months. Conclusions: In ultrasound-guided popliteal sciatic nerve block, intraneural injection provided a faster onset and better success rate compared with subparaneural. Both techniques resulted in a similar subclinical reduction in amplitude of the sciatic action potentials at 5 weeks after surgery. These findings should not be extended to other approaches. Abstract : Supplemental digital content is available in the text.